2016
DOI: 10.1002/hep.28933
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated neddylation in liver fibrosis

Abstract: Hepatic fibrosis is a global health problem currently without effective therapeutic approaches. Even though the ubiquitin-like post-translational modification of neddylation, that conjugates Nedd8 to specific targets, is aberrant in many pathologies, its relevance in liver fibrosis remained unexplored. Our results show deregulated neddylation in clinical fibrosis and both in mouse bileduct ligation (BDL)-and carbon tetrachloride (CCl 4 )-induced fibrosis. Importantly, neddylation inhibition, by using the pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 45 publications
(98 reference statements)
4
61
0
Order By: Relevance
“…In the pathology of liver fibrosis and in cholestatic liver injury different types of hepatic cells including hepatocytes, cholangiocytes, inflammatory macrophages (Kupffer cells) 16 and Natural Killer 7 , 17 19 cells, and hepatic stellate cells (HSC) 20 are known to mediate different effects, regulating the development and the progression of the disease. During initiation of fibrogenesis, hepatocyte apoptosis and cholangiocyte proliferation are the primary events driving disease progression 14 .…”
Section: Resultsmentioning
confidence: 99%
“…In the pathology of liver fibrosis and in cholestatic liver injury different types of hepatic cells including hepatocytes, cholangiocytes, inflammatory macrophages (Kupffer cells) 16 and Natural Killer 7 , 17 19 cells, and hepatic stellate cells (HSC) 20 are known to mediate different effects, regulating the development and the progression of the disease. During initiation of fibrogenesis, hepatocyte apoptosis and cholangiocyte proliferation are the primary events driving disease progression 14 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, cirrhosis can also evolve to hepatocellular carcinoma (HCC) with poorer survival rates [13]. HCC is the most prevalent form of presentation (70%-85%) of liver cancer, which is the fifth most common cancer type in the world and the second cause of cancer-related death [14,15].…”
Section: Non-alcoholic Fatty Liver Disease and Derived Hepatocellularmentioning
confidence: 99%
“…Regarding their effect in the hepatocyte, both an upregulated A-SMase expression and ceramide content have been related to cell death [89] through activation of death receptors as fatty acid synthase (FAS) and TNFR1 [95]. The induction of necrosis in CCl 4 -treated mice, a fibrosis model widely studied [13,96], has been also correlated with an increase of ceramide content both in serum and liver [97]. Correlated with TNF, previously cited to deplete GSH levels in the cell during NASH, hepatocytes have been described to be more susceptible for cell death in that context [98,99].…”
Section: Ceramide and S1p Role In Fibrosis And Cirrhosis Developmentmentioning
confidence: 99%
“…Activation of NADPH oxidases (NOXs) induces HSCs activation ( Jiang et al, 2010 ), and inhibition of NOX1/NOX4 has been shown to suppress fibrogenesis in the bile duct ligation (BDL) and CCl 4 models ( Aoyama et al, 2012 ; Crosas-Molist and Fabregat, 2015 ). The immune response, that has multiple interactions with the fibrogenic process, may be also a candidate for therapy ( Pellicoro et al, 2014 ); thus, several strategies to block the TGF-β activity have shown efficacy ( Vogt et al, 2011 ; Rogler et al, 2017 ), and inhibition of chemokines and their receptors demonstrated antifibrotic effects in rodent models of liver fibrosis ( Zaldivar et al, 2010 ; Seifert et al, 2015 ; Zubiete-Franco et al, 2017 ).…”
Section: Mechanisms Involved In the Pathogenesis Of Liver Fibrosismentioning
confidence: 99%